2007
DOI: 10.1108/01443570710742393
|View full text |Cite
|
Sign up to set email alerts
|

Internal supply chain management in the Chilean sawmill industry

Abstract: PurposeThe existing business paradigm in the sawmill industry is that improvements are achieved by enhancements at each individual sawmilling plant. The authors investigate a collaborative approach, and propose a model for optimizing production and inventory planning decisions within a system of plants.Design/methodology/approachThe methodology models the sawmill production process in terms of two transformation stages and two inventory stages. The authors then extend the model to account for supply chain deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…For example, a study on Quebec mills, showed that by effectively managing all nodes in a supply chain, the overall cost can decrease [37]. Another study in the Chilean sawmill industry found that internal supply chain management would increase the profitability of the sawmills by approximately 15% [38]. Ronnqvist [39] conducted an extensive review of literature to define the set of decisions that need to be made in a wood products supply chain, and concluded that operations research (OR) and especially optimization can be used as decision support tools in forestry.…”
Section: Forest Products Industry Supply Chain Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study on Quebec mills, showed that by effectively managing all nodes in a supply chain, the overall cost can decrease [37]. Another study in the Chilean sawmill industry found that internal supply chain management would increase the profitability of the sawmills by approximately 15% [38]. Ronnqvist [39] conducted an extensive review of literature to define the set of decisions that need to be made in a wood products supply chain, and concluded that operations research (OR) and especially optimization can be used as decision support tools in forestry.…”
Section: Forest Products Industry Supply Chain Modelsmentioning
confidence: 99%
“…There has been a lot of emphasis on supply chain management in the forest industry as a result of consolidation of upstream and downstream companies [37,38]. The studies focus on each of the operational areas in the forest industry separately, examining the effect of different management scenarios on the performance of individual companies as well as the entire sector in different regions and countries.…”
Section: Forest Products Industry Supply Chain Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the problem has been formulated in literature in a similar way, in some cases it has been combined with bucking decisions Adams 1991, Maness andNorton 2002) and timber transfer decisions among plants in a supply chain context (Singer and Donoso 2007). In Todoroki and Rönnqvist (2002), a sawing optimization model is implemented in a sawing simulator hence the optimal cutting pattern is determined on a log-by-log basis; an approach that does not find the optimal log-pattern mix that best satisfies the customer demand.…”
Section: Introductionmentioning
confidence: 99%
“…In Todoroki and Rönnqvist (2002), a sawing optimization model is implemented in a sawing simulator hence the optimal cutting pattern is determined on a log-by-log basis; an approach that does not find the optimal log-pattern mix that best satisfies the customer demand. Multi-period models (Maness and Norton 2002, Singer and Donoso 2007, Maturana et al 2010 have also been used with the possibility of handling inventory, of either logs or lumber, to add more flexibility. Maturana et al (2010) compare a sawing optimization model with a heuristic that emulates the decision behavior of the sawmill scheduler.…”
Section: Introductionmentioning
confidence: 99%